1996
DOI: 10.1097/00007632-199601010-00020
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in the Measurement of Bone Mineral Density by Dual Energy X-ray Absorptiometry

Abstract: The effect of volume on bone mineral density data based on projectional areas can cause very significant perturbations of the data in biomechanical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…The advantages of DXA, such as cost efficiency, noninvasiveness, and low radiation exposure for patients, have led to a widespread availability of DXA and frequent usage by clinicians. However, several authors have demonstrated disadvantages of DXA, such as distortion of values in estimating actual bone mass and interference by body composition and patient age (4)(5)(6). While DXA can provide an accurate BMD measurement in vitro (eg, vertebrae in a homogeneous fluid) (7), in vivo analysis is impaired by overlying soft tissue, vascular calcifications, bowel contents, and degenerative spine changes (6,8).…”
Section: Patient Selection and Study Designmentioning
confidence: 99%
“…The advantages of DXA, such as cost efficiency, noninvasiveness, and low radiation exposure for patients, have led to a widespread availability of DXA and frequent usage by clinicians. However, several authors have demonstrated disadvantages of DXA, such as distortion of values in estimating actual bone mass and interference by body composition and patient age (4)(5)(6). While DXA can provide an accurate BMD measurement in vitro (eg, vertebrae in a homogeneous fluid) (7), in vivo analysis is impaired by overlying soft tissue, vascular calcifications, bowel contents, and degenerative spine changes (6,8).…”
Section: Patient Selection and Study Designmentioning
confidence: 99%
“…We hypothesized that this technique may also be applied to targeted BMD assessment of the cancellous bone of the vertebral pedicle which is not assessed with dual-energy x-ray absorptiometry (DXA) routinely performed for evaluation of BMD and detection of osteoporosis [12]. Preoperative evaluation of pedicle BMD may be beneficial as the trabecular architecture of the lumbar pedicle is different from that of the vertebral body [13].…”
Section: Introductionmentioning
confidence: 99%
“…57 The modality inherits a variety of advantages compared with dual-energy X-ray absorptiometry (DXA), 8,9 the modality currently implemented in the World Health Organization definition of osteoporosis. 10 Because many patients undergo abdominal multidetector CT (MDCT) for clinical reasons, routine MDCT-derived measurements may lead to a redundancy of additional quantitative CT (QCT) scans and thus minimize radiation exposure and health care costs.…”
mentioning
confidence: 99%